Molecular systematics and taxonomic status of three latitudinally widespread nototheniid (Perciformes: Notothenioidei) fishes from the Southern Ocean - Miya, Tshoanelo; Gon, Ofer; Mwale, Monica; Poulin, Elie (Zootaxa, 2016)
The taxonomic status of the three nototheniids, Lepidonotothen squamifrons, L. larseni and Gobionotothen marionensis from different localities in the Southern Ocean is re-evaluated at the DNA level. DNA sequence divergences and phylogenetic relationship were estimated using a combined mitochondrial (mtDNA, ND2 and COI) dataset and data for one nuclear gene (S7 intron 1). Phylogenies of both datasets had Lepidonotothen kempi nested within L. squamifrons lineage, with low sequence divergences (0% to 0.4%) between the two nominal species suggesting that they are populations of one species. Therefore, these results do not support the previous splitting of L. squamifrons into different species. Similarly, the L. larseni specimens also represented a single genetic unit (0.3% to 0.6%) with low geographic variation between Atlantic and Indian Ocean specimens, which does not support the splitting of this species into geographically restricted species. The mtDNA phylogeny clearly separated individuals of G. acuta from Kerguelen, Heard and MacDonald Islands from G. marionensis individuals into different clades, with sequence divergence of 2.9% between these clades supporting they are different species.